PENGARUH MODEL PEMBELAJARAN INKUIRI SOSIAL UNTUK MENINGKATKAN KEPEKAAN SOSIAL PESERTA DIDIK (Studi Quasi Eksperimen dalam Pembelajaran IPS di Kelas V MI) - Tusriyanto, Tusriyanto (P3M STAIN Jurai Siwo Metro, 2013)
Social studies elementary school should be emphasized in social sensitivity skills in social life. Social studies has a value of practical learning, which should foster individual creative, democratic and responsible, as well as coaching and also have the burden of cultural as well as a good life, harmonious and dynamic. Social studies educators should be aware that educate participants who would implement any content social studies and social life tomorrow will be different from today. The aim of this study, is